Singapore hotels : an environmental profile - Choo Tze Wei (2008)
Environmental issues are of growing importance in the industrial and business world. The hospitality industry, being one of the largest industries in the world, is not immune to environmental problems. In Singapore, there is a growing concern among businesses to incorporate the environmental factors to achieve service excellence. Hotels, in particular, are already fulfilling both the legal and environmental obligations through various conservation programmes. The objective of this research is to identify management, staff and guests' awareness and views on environmental practices of hotels in Singapore. Since little research was done on this topic, we conducted surveys on these three groups of people in order to achieve the above objective. In addition the survey results aim to give us a better insight of the environmental profile fo hotels in Singapore.